Kalaba Road (Sivrice-Elazig) Landslide and Susceptibility Analysis - Sengun, M. Taner; Saman, Busra; Karadeniz, Enes (Istanbul Univ Press, Istanbul Univ Rectorate, 2019)
Landslides are one of the most important disasters in our country that pose a risk to life and property safety. The landslide events frequently seen in our country have coused damage to settlements and transport networks. With the landslide susceptibility analysis, these losses aims to minimize. The study area is located in the basin of the district of Sivrice, Elazig province where landslide activities are common. Landslide accured on April 4, 2019 on the road to Kalaba village in the basin and approximately 15 village roads were closed for transportation. On the field of landslide have been nearly found landslides. The area where the road passes is a high risk region for landslides. Purpose of research, factors that are effective on the formation of the landings on the road of Kalaba village (lithological structure of the field, tectonic activity) in consideration, landslides were assessed, landslide susceptibility analyses were conducted with various Geographic Informtion System applications. In this study, the risky region in the Kurk River Basin, which is in the danger of landslide, Google Earth images for settlements and transportation networks, ArcGIS 10.5 program and field observations were used. In this context, sensitivity maps of landslide field were produced by using Analytic Hierarchy Process (AHP) and Weighted Overlay in Geographic. In light of the data obtained at the end of the study, risky areas have been determined by taking into consideration the past and present landslides and necessary suggestions are presented.
1st Istanbul International Geography Congress -- JUN 20-22, 2019 -- Istanbul, TURKEY
Keywords: Kurk River Basin; Landslide; Analytic Hierarchy Process(AHP)